Pollution, Infectious Disease, and Mortality: Evidence from the 1918 Spanish Influenza Pandemic. (2nd December 2018) - Clay, Karen; Lewis, Joshua; Severnini, Edson
Abstract : The 1918 Influenza Pandemic killed millions worldwide and hundreds of thousands in the United States. This article studies the impact of air pollution on pandemic mortality. The analysis combines a panel dataset on infant and all-age mortality with a novel measure of air pollution based on the burning of coal in a large sample of U.S. cities. We estimate that air pollution contributed significantly to pandemic mortality. Cities that used more coal experienced tens of thousands of excess deaths in 1918 relative to cities that used less coal with similar pre-pandemic socioeconomic conditions and baseline health. Factors related to poverty, public health, and the timing of onset also affected pandemic mortality. The findings support recent medical evidence on the link between air pollution and influenza infection, and suggest that poor air quality was an important cause of mortality during the pandemic.